Is There a Delay in Diagnosis of Duchenne Muscular Dystrophy Among Preterm-Born Males?. (July 2018) - Soim, Aida; Smith, Michael G.; Kwon, Jennifer M.; Mann, Joshua R.; Thomas, Shiny; Ciafaloni, Emma; ,
The objective of this study was to investigate whether males who were born preterm took longer to receive a Duchenne muscular dystrophy diagnosis than term males. Data for males with Duchenne muscular dystrophy identified through a population-based surveillance system were analyzed using a Kaplan-Meier estimator. The first signs and symptoms were noted at a median age of 2 years in both groups. Median age when first signs and symptoms prompted medical evaluation was 2.59 years among preterm and 4.01 years among term males. Median age at definitive diagnosis was 4.25 years and 4.92 years for preterm and term males, respectively. Neither difference was statistically significant. Preterm males tended to be seen for their initial medical evaluation earlier than term males, though they were not diagnosed significantly earlier. It may take clinicians longer after the initial evaluation of preterm males to arrive at a Duchenne muscular dystrophy diagnosis.